A novel vapor-compression refrigeration loop for high ambient temperatures. (October 2016) - Ribeiro, Guilherme B.
Highlights: A novel refrigerating loop was created for the compressor thermal management. The proposed cooling unit was compared with two thermoelectric units. The novel loop allows the unit to operate under ambient temperatures up to 55 °C. The proposed unit presented COP two times higher than the thermoelectric units. Abstract: Refrigeration equipment as the compressor has had its size reduced and cooling capacity increased in the last years, which leads to a continuous rise of the level of heat flux dissipated through the compressor shell and may cause reliability issues related to the compressor's moving parts. Furthermore, extreme conditions as high ambient temperatures augment the importance of keeping the compressor shell temperature under safe limits. To overcome such difficulties, a novel vapor-compression refrigerating loop was created especially for the compressor thermal management. A cooling unit was assembled using the proposed loop and later compared experimentally with two thermoelectric coolers under ambient temperatures of 25, 35 and 55 °C. The results have shown that the novel refrigerating loop enables the vapor-compression unit to work at a high ambient temperature (55 °C) and nearly a two times higher coefficient of performance (COP) was achieved, when compared to thermoelectric solutions.